Hepatic stellate cells control liver zonation, size and functions via R-spondin 3 - Sugimoto, Atsushi; Saito, Yoshinobu; Wang, Guanxiong; Sun, Qiuyan; Yin, Chuan; Lee, Ki Hong; Geng, Yana; Rajbhandari, Presha; Hernandez, Celine; Steffani, Marcella; Qie, Jingran; Savage, Thomas; et al. (Nature, 2025)
Hepatic stellate cells (HSCs) have a central pathogenetic role in the development of liver fibrosis. However, their fibrosis-independent and homeostatic functions remain poorly understood1-5. Here we demonstrate that genetic depletion of HSCs changes WNT activity and zonation of hepatocytes, leading to marked alterations in liver regeneration, cytochrome P450 metabolism and injury. We identify R-spondin 3 (RSPO3), an HSC-enriched modulator of WNT signalling, as responsible for these hepatocyte-regulatory effects of HSCs. HSC-selective deletion of Rspo3 phenocopies the effects of HSC depletion on hepatocyte gene expression, zonation, liver size, regeneration and cytochrome P450-mediated detoxification, and exacerbates alcohol-associated and metabolic dysfunction-associated steatotic liver disease. RSPO3 expression decreases with HSC activation and is inversely associated with outcomes in patients with alcohol-associated and metabolic dysfunction-associated steatotic liver disease. These protective and hepatocyte-regulating functions of HSCs via RSPO3 resemble the R-spondin-expressing stromal niche in other organs and should be integrated into current therapeutic concepts.